Peripheral neuropathy in stable chronic obstructive pulmonary disease: Is the phrenic nerve more affected compared with other peripheral nerves? - Atef W El-Rifai; Sherif M El-Shazli (Wolters Kluwer Medknow Publications, 2017)
Background Chronic obstructive pulmonary disease (COPD) is a multicomponent disease with extrapulmonary manifestation. Peripheral nerve affection may be one of the results or mechanism of COPD. Objective The aim of this study was to evaluate peripheral neuropathy in patients with stable COPD and whether these changes are more or less marked in the phrenic nerve when compared with other peripheral nerves. Patients and methods Eighty patients with COPD and 60 healthy individuals as a control group were included. All were subjected to the following: (i) full history taking; (ii) clinical and neurological examination; (iii) chest radiography; (iv) high-resol ution computed tomography scanning of the chest; (v) arterial blood gases analysis at room air; and (vi) spirometric tests. Results There was a statistically significant increase in smoking packs/year, respiratory rate, hemoglobin, and white blood cells in the COPD group. There was a significant decrease in oxygen saturation, pH, arterial oxygen tension, forced expiratory volume in 1 s, forced expiratory volume in 1 s/forced vital capacity, and forced vital capacity% in the study group when compared with the control group, whereas there was a significant increase in CO2 tension in the COPD group. There was a significant increase in the distal latency of all nerves and a significant decrease in the amplitude and conduction velocity of all nerves, except the amplitude of the phrenic nerve in the COPD group. The difference for phrenic nerve amplitude was statistically nonsignificant. In the COPD group, abnormal motor activity in the median, ulnar, common peroneal, and phrenic nerves of 30, 22.5, 35, and 22.5%, respectively, was reported, whereas abnormal sensory activity in the median, ulnar, and sural nerves of 30.0, 27.5, and 42.5%, respectively, was reported. Finally, we found a statistically significant increase in nerve abnormalities with increased severity of the disease. Conclusion COPD had a significant affection on peripheral nerves, either motor or sensory. In addition, COPD had a significant affection on the phrenic nerve and muscle of the diaphragm. However, this affection of the phrenic nerve was confined to grades III and IV and was the least affection of studied nerves.